A rare case of trapezium osteochondroma: unveiling a unique tumour with clinical implications - N. R., Fijad; Mammu, Sharafuddeen; Ravindran, M. K.; V. K., Vaishak; Gopi, Jipin (International Journal of Research in Orthopaedics, 2024)
Osteochondroma is a benign bone tumour commonly found on the metaphysis of long bones. The presentation of osteochondroma on the trapezoid bone, a carpal bone in the wrist, is exceptionally rare. To our knowledge, no such cases have been reported in India. This report details a rare case of osteochondroma located on the trapezoid bone and its successful surgical management. A 55-year-old female presented with pain and swelling in the wrist. Radiological imaging, including X-rays and MRI, revealed a well-defined, pedunculated mass arising from the trapezoid bone. The patient underwent surgical resection of the tumour. Histopathological examination confirmed the diagnosis of osteochondroma. Postoperatively, the patient experienced significant relief from symptoms and showed no evidence of tumour recurrence during follow-up. This case contributes to the limited body of literature on osteochondromas in rare locations, particularly on the trapezoid bone. It illustrates the successful outcome of surgical treatment for rare bone tumours and emphasizes the need for heightened awareness and comprehensive diagnostic approaches in similar cases.